DIABETES MELLITUS GYMNASTICS IMPACTS RESILIENCE AND STRESS LEVELS: FACT OR MYTH? - Hartanto, Agung Eko; Hendrawati, Gandes Widya; Purwaningsih, Yustina (Indonesian Journal of Health Science, 2024)
Diabetes Mellitus type II is a condition of increased blood glucose caused by disturbances in insulin resistance and insulin secretion that causes metabolic disorders of the body, is a silent killer disease. Living with DM causes stress in a person because most of the patient's time is spent on treatment. It is estimated that around 1.6 million deaths are caused by diabetes globally. Decreased quality of life often occurs in patients with chronic diseases, one of which is DM which has an impact on stress and resilience. The purpose of this study was to determine the effect of Diabetes Exercises on the level of stress and resilience of DM sufferers. This study used a Quasy Experimental design (pre- and post-test), involving 20 intervention groups and 20 control groups taken with purposive sampling techniques. The paired sample t-test results showed a p-value of 0.448 which means there was no difference before and after DM Exercise to stress and resilience. DM Exercise indirectly does not affect the resilience and stress of DM sufferers, it contributes to reducing the stress of DM patients. In future studies, it is expected that Diabetes Resilience Training and Mindfulness actions in DM patients to improve their quality of life